Trao quyền cho phụ nữ trong phát triển du lịch biển bền vững: Sự kết hợp giữa lý thuyết hành vi dự định và lý thuyết trao quyền - Phạm Thị Bích, Duyên; Nguyễn Hoàng, Phong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study analyzes women’s intention to support sustainable coastal tourism development in Vietnam’s South Central Coast, drawing on the Theory of Planned Behavior combined with Empowerment Theory. A stratified and purposive sampling strategy was applied to collect data from 527 women working in various marine tourism sectors, ensuring diversity in contexts and occupations. The PLS-SEM analysis reveals that attitude toward behavior, subjective norms, perceived behavioral control, and empowerment all have significant positive effects on supportive intention, with attitude serving as a key mediating factor. The findings extend the application of Theory of Planned Behavior in the marine tourism context, highlight the pivotal role of women’s empowerment in promoting sustainable tourism development, and provide additional evidence on the mediating mechanism of behavioral attitude and the contribution of multidimensional empowerment strategies.